2006
DOI: 10.1080/03050620600574873
|View full text |Cite
|
Sign up to set email alerts
|

Time to Go? Duration Dependence in Forced Migration

Abstract: In this paper we introduce some theoretical and methodological refinements to account for effects of duration dependence in forced migration flows that have not been noticed in previous research. The engine of previous theoretical arguments on forced migration has been a decision theoretic model in which the potential migrants estimate the threat to their security and then weigh this threat against costs and benefits of leaving. Moreover, in previous arguments and empirical tests the costs and benefits for rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 23 publications
5
60
0
Order By: Relevance
“…Moore and Shellman (2007) focus on the direction of refugee flights, finding that refugees move to places that are free of conflict, where incomes are higher and where the costs of transit are lower. Melander and Öberg (2006) analyse the persistence in displacements, arguing that the flows tend to decrease when those most able or willing to move have left. They also found that outflows are reduced by regime transition in the origin country but increased by regime collapse.…”
Section: Analysing Refugee and Asylum Seeker Movementsmentioning
confidence: 99%
“…Moore and Shellman (2007) focus on the direction of refugee flights, finding that refugees move to places that are free of conflict, where incomes are higher and where the costs of transit are lower. Melander and Öberg (2006) analyse the persistence in displacements, arguing that the flows tend to decrease when those most able or willing to move have left. They also found that outflows are reduced by regime transition in the origin country but increased by regime collapse.…”
Section: Analysing Refugee and Asylum Seeker Movementsmentioning
confidence: 99%
“…On the other hand, other aggregate studies showed that migration was strongly predicted by political violence, independent of the economic circumstances (Davenport, Moore, and Poe 2003;Melander and Öberg 2006;Moore and Shellman 2004;Morrison 1993;Morrison and Perez-Lafauri 1994;Schmeidl 1997;Shellman and Stewart 2007). Some studies at the household level also showed consistent results, suggesting that violence was strongly related to out-migration and remained so under a variety of controls (Engel and Ibânez 2007).…”
Section: Migration and The Unrest In Prior Researchmentioning
confidence: 53%
“…Empirical results remain unclear, however. Some studies use GNP and GDP per capita as proxies for economic opportunity, but these variables did not significantly predict forced migration (Davenport, Moore, and Poe 2003;Melander and Öberg 2006). By contrast, other studies find that countries with higher levels of economic development tend to produce fewer refugees (Moore and Shellman 2004;Schmeidl 1997).…”
Section: Migration and The Unrest In Prior Researchmentioning
confidence: 99%
“…However, we do offer an indirect test of this proposition: If the ratio of civilian to military victims has changed, when comparing conflicts with similar levels of battle severity from the Cold War and post-Cold War periods, we should expect to see higher numbers of civilian deaths in the latter. Moreover, if the ratio of civilian to military deaths is higher in the post-Cold War period then ipso facto conflicts have become more threatening and dangerous to civilians, which research on forced migration has consistently shown should generate higher levels of civilian displacement (Davenport et al, 2003;Melander, 2006;Melander and Öberg, 2006;Moore and Shellman, 2002;Schmeidl, 1997). By holding battle severity constant and looking at the variation in civilian displacement and civilians killed, we test whether or not the ratio has changed significantly over time.…”
Section: The Severity Of Battle In Civil Conflicts Is Increasing; (2)mentioning
confidence: 99%
“…Our previous research has identified several additional controls relating to temporal dependence in forced migration that are relevant when this dependent variable is concerned (Melander and Öberg, 2006).…”
Section: Temporal Dependencementioning
confidence: 99%